2018
DOI: 10.1111/joic.12563
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient mortality and its predictors after pericardiocentesis: An analysis from the Nationwide Inpatient Sample 2009–2013

Abstract: Background: National registries have provided data on in-hospital outcomes for several cardiac procedures. The available data on in-hospital outcomes and its predictors after pericardiocentesis are mostly derived from single center studies.Furthermore, the outcomes after pericardiocentesis for iatrogenic pericardial effusion and the impact of procedural volume on in-hospital outcomes in the United States are largely unknown.Methods: We used national inpatient database files for the years 2009-2013 to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Pericardiocentesis may be associated with minor and major complications that include but are not limited to: pneumothorax, catheterization of the wrong site and/or organ, cardiac puncture, coronary artery laceration, massive hemorrhage, and intra‐procedural death . Studies reporting the risk of complications with pericardiocentesis have variable findings with some studies showing complication rates as low as 1.2% while others reporting an increased risk of complications and mortality as high as 18% . The significance of understanding the utilization patterns of pericardiocentesis nationwide is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardiocentesis may be associated with minor and major complications that include but are not limited to: pneumothorax, catheterization of the wrong site and/or organ, cardiac puncture, coronary artery laceration, massive hemorrhage, and intra‐procedural death . Studies reporting the risk of complications with pericardiocentesis have variable findings with some studies showing complication rates as low as 1.2% while others reporting an increased risk of complications and mortality as high as 18% . The significance of understanding the utilization patterns of pericardiocentesis nationwide is important.…”
Section: Introductionmentioning
confidence: 99%
“…Pericardiocentesis associated with different cardiac procedures [Color figure can be viewed at wileyonlinelibrary.com] possible complication that is often treated with pericardiocentesis.However, due to the complex and comorbid condition of that patient subset and the concurrent medications used, the risk of cardiac tamponade is exceptionally high in cases with iatrogenic effusion due to the acute accumulation of blood and fluids in the pericardium further complicating patient status and worsening outcomes. One singlecenter study found high mortality among patients undergoing percutaneous aortic valve repair (TAVR) that was reported as approximately one in every four in cases that developed cardiac tamponade 9. Yet, another study reported lower mortality numbers in patients undergoing electrophysiologic procedures (EP) 18.…”
mentioning
confidence: 99%
“…Our region shows similar characteristics to the literature in terms of cancer prevalence detected in patients who underwent pericardiocentesis. In our study, cancer was diagnosed in 24 (26%) patients; this rate was reported between 25.3-31.5% in large-scale cohort studies 12,2,6 . In addition, lung cancer is the most common malignancy (54%) in our region, it has been reported between 44-52.9% in the literature 12,2,6 .…”
Section: Discussionmentioning
confidence: 45%
“…In addition, lung cancer is the most common malignancy (54%) in our region, it has been reported between 44-52.9% in the literature 12,2,6 . In parallel with other studies evaluating inpatient mortality, it was found higher in cancer patients in our study also 6,12 . Recently, pericardial effusion and tamponade due to tuberculosis have not been reported in developed countries, nor were they detected in the patient population we evaluated.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation